Comparative Study on some Organic Manure Commonly Used in Aquaculture - Chakrabarty, D. (Our Nature, 2010)
Assorted physical and chemical parameters were measured in glass aquaria (10 l) receiving some commonly used organic manure namely cow dung (CD), compost charged with rock phosphate (CR), vermin-compost charged with rock phosphate (VCR), horse dung (HD) and farm yard manure (FYM). There was no significant difference in the moisture content of the manures tested. The values of pH, conductance, TDS, PO4-P, NH3-N was highest in the VCR treatment indicating a better manurial value for VCR than others. The size of fibers of VCR was significantly (P>0.05) lower in size when compared with other manures tested. There was almost no difference in fiber content of the manures tested except VCR where it was significantly low (p<0.05) than other four. The different organic manures used can be graded in the following descending order in manurial value as direct application manure: VCR (T3) > CD (T1) > CR (T2) > HD (T4) > FYM (T5). The values of total suspended solids (TSS) imparted by the manures showed significant differences (P>0.05) among various treatments and was in the following descending order: HD (T4) > CD (T1) > CR (T2) > FYM (T5) > VCR (T3). This indicates that the application of (VCR) will pass on less fiber garbage to aquatic body. Key words: Limnology, aquaculture, vermi-compost, organic manure, rock phosphate DOI: 10.3126/on.v7i1.2566 Our Nature (2009) 7:163-167